2015
DOI: 10.1021/ac5037523
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reaction Monitoring of Negative Electrospray Ionization Acetate Adduct Ions for the Bioanalysis of Dapagliflozin in Clinical Studies

Abstract: Dapagliflozin (Farxiga), alone, or in the fixed dose combination with metformin (Xigduo), is an orally active, highly selective, reversible inhibitor of sodium-glucose cotransporter type 2 (SGLT2) that is marketed in United States, Europe, and many other countries for the treatment of type 2 diabetes mellitus. Here we report a liquid chromatography-tandem mass spectrometry (LC-MS/MS) bioanalytical assay of dapagliflozin in human plasma. A lower limit of quantitation (LLOQ) at 0.2 ng/mL with 50 μL of plasma was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…They further observed that, in the presence of formate or acetate ions, the corresponding adduct became more abundant, which reduced the sensitivity of detection. On the contrary, the work of Ji et al () showed the formation of acetate ion adducts of DAPA ( m/z 467) in the negative mode with higher intensity compared with the [M − H] − ions. The same observation was found in the present work.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…They further observed that, in the presence of formate or acetate ions, the corresponding adduct became more abundant, which reduced the sensitivity of detection. On the contrary, the work of Ji et al () showed the formation of acetate ion adducts of DAPA ( m/z 467) in the negative mode with higher intensity compared with the [M − H] − ions. The same observation was found in the present work.…”
Section: Resultsmentioning
confidence: 92%
“…The Q1 MS spectra in the positive mode showed the predominant protonated molecular ions [M + H] + at m/z 130.1 and 136.1 for MET and MET‐d6, while the most consistent product ions were observed at m/z 60.1 for MET and MET‐d6, respectively. For DAPA, both positive as well as negative ionization modes were investigated as both are studied in reported methods (Aubry et al, ; Ji et al, ). It was observed that the nature of mobile phase significantly affects the type of ion formation and their intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Madhavi et al [31] has described a rapid, an accurate and precise Ultra Performance Liquid Chromatography (UPLC) method for simultaneous estimation of Saxagliptin and Dapagliflozin in its tablet dosage form (10mg Dapagliflozin and 5mg Saxagliptin). The UPLC method was developed using 2.1 × 100 mm, reverse phase C18 column (Acquity UPLC ethylene bridge hybrid (BEH) C18 1.7 μm).…”
Section: Rp-uplc Methods For Determination Of Dapagliflozinmentioning
confidence: 99%
“…There are some reported spectrophotometric methods for DGF assay either in raw material or in its pharmaceutical dosage forms [5][6][7][8][9] , however these methods have low sensitivity and cannot be applied for analysis of DGF in complexed biological samples such as human plasma. In the published literature, there are some reported high performance liquid chromatography (HPLC) methods for analysis of DGF in both its pure and tablet forms, as well as in biological fluids [10][11][12][13][14][15][16][17][18][19] , however the reported HPLC methods are complex and expensive. Therefore, a new simple and sensitive spectroscopic method was required to achieve the aim of this study.…”
Section: Introductionmentioning
confidence: 99%